Optimization of operating parameters in microbial consortium (AB-101) preparation and application in palm oil mill effluent (POME) primary treatment - Abidi, Muhammad Adib (2022)
Polluting characteristics of palm oil mill effluent (POME) urge palm oil mills to implement numerous technologies to further treat POME after the primary treatment system to comply the effluent discharge standard limit posed by Department of Environment (DOE) Malaysia. However, microbial consortium (AB-101), a dark-brown liquid fermented product of various type of fruits and plants was introduced to improve the conventional biological treatment process in order to comply the standard without tertiary treatment. It is mixed with selective nutrients and effluent to prepare end product (bio-activator) that is inoculated into anaerobic ponds of POME to enhance anaerobic digestion. Therefore, the purpose of this research is to evaluate and optimize the operating parameters in microbial consortium (AB-101) application, such as; (i) volume percentage of AB-101 in bio-activator preparation process; (ii) volume percentage of molasses in bio-activator preparation process molasses; and (iii) dosage of the bio-activator. The optimization of these operating parameters is conducted via Response Surface Methodology (RSM). Meanwhile the evaluation and comparison of AB-101 performance under original and optimized operating parameters are based on physico-chemical characteristics of treated POME. The optimum operating parameters values obtained were as follows; 0.01 % v/v of AB-101 in bio-activator, 9.96 % v/v of molasses in bio-activator; and 43.8 ppm of bio-activator dosage. These optimum operating parameters resulted in the following POME characteristics reduction percentage: biochemical oxygen demand (BOD) = 92.9%, chemical oxygen demand (COD) = 65.3%, total suspended solid (TSS) = 93.4% and oil and grease = 95.5%.